Communication And Communicative Aim - Umarova Zumradxon Avazxon qizi (Miasto Przyszłości, 2024)
This paper explores the intricate relationship between communication and communicative aim. Communication, a fundamental human process, serves various purposes, including the transmission of information, the expression of emotions, and the creation of social bonds. The paper analyzes different communicative aims and how they influence the process and effectiveness of communication. Through a comprehensive review of relevant literature, this study sheds light on the dynamics of communication in diverse contexts. The findings underscore the importance of context in shaping communicative aims and offer insights for future research.